2009
DOI: 10.1158/1078-0432.ccr-09-0506
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Endometrial Tumorigenesis: Importance of Complex Hyperplasia Regardless of Atypia

Abstract: Purpose: Endometrial carcinoma (EC) is common in the population and the most frequent extracolonic malignancy in hereditary nonpolyposis colorectal carcinoma (HNPCC)/Lynch syndrome. We characterized precursor lesions of endometrioid EC to identify markers of malignant transformation and tumor progression. Experimental Design: Serial specimens of normal endometrium, simple hyperplasia, complex hyperplasia without atypia, complex hyperplasia with atypia, and endometrial carcinoma obtained during a 10-year survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 39 publications
(42 reference statements)
6
53
0
3
Order By: Relevance
“…We showed that miR-129-2 methylation stratified endometrial specimens into two groups, one with low methylation (normal endometrium and SH) and another one with a significantly higher methylation (CH and CAH). It remains controversial which lesions should be considered as precursors to EC, and the miRNA data, together with our previous findings of conventional TSGs [27], support the importance of complex hyperplasia, with or without atypia, as a precursor lesion of EC.…”
Section: Discussionsupporting
confidence: 55%
“…We showed that miR-129-2 methylation stratified endometrial specimens into two groups, one with low methylation (normal endometrium and SH) and another one with a significantly higher methylation (CH and CAH). It remains controversial which lesions should be considered as precursors to EC, and the miRNA data, together with our previous findings of conventional TSGs [27], support the importance of complex hyperplasia, with or without atypia, as a precursor lesion of EC.…”
Section: Discussionsupporting
confidence: 55%
“…12 Although these patients had a germline predisposition for the development of MSI, the data do suggest that MSI may be present early in endometrial carcinogenesis.…”
Section: Discussionmentioning
confidence: 80%
“…The frequency of MSI-H in ovarian cancer was significantly higher than that in endometriosis. In addition, endometriosis also displayed a high frequency of MSI compared with the normal endometrium, in which its frequency has been reported to be lower than 5% [25]. MMR deficiency has been reported to be an important tumorinitiating mechanism in both endometrial and ovarian carcinomas [26].…”
Section: Discussionmentioning
confidence: 99%